2015
DOI: 10.4064/sm226-1-3
|View full text |Cite
|
Sign up to set email alerts
|

Triple derivations on von Neumann algebras

Abstract: It is well known that every derivation of a von Neumann algebra into itself is an inner derivation and that every derivation of a von Neumann algebra into its predual is inner. It is less well known that every triple derivation (defined below) of a von Neumann algebra into itself is an inner triple derivation.We examine to what extent all triple derivations of a von Neumann algebra into its predual are inner. This rarely happens but it comes close. We prove a (triple) cohomological characterization of finite f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Jordan weak amenability is deeply connected with the more general notion of ternary weak amenability (see [25]). More interesting results on ternary weak amenability were recently developed by R. Pluta and B. Russo in [34].…”
Section: Jordan Derivationsmentioning
confidence: 95%
“…Jordan weak amenability is deeply connected with the more general notion of ternary weak amenability (see [25]). More interesting results on ternary weak amenability were recently developed by R. Pluta and B. Russo in [34].…”
Section: Jordan Derivationsmentioning
confidence: 95%
“…The following theorem provides some significant infinite dimensional examples of Lie algebras in which every derivation is inner. Its proof is in the spirit of [28]. Proof.…”
Section: Cohomology Of Lie Algebras With Involutionmentioning
confidence: 98%
“…By the theorem of Sinclair [33], S 0 is a derivation and by the theorems of Kadison and Sakai, [18,30], S 0 is an inner derivation, say S 0 (x) = ax − xa for some a ∈ V . By well known structure of the span of commutators in von Neumann algebras due to Pearcy-Topping, Halmos, Halpern, Fack-de la Harpe, and others (see [28] for the references), a = z + [c i , d i ], where c i , d i ∈ V and z belongs to the center of V . It follows that…”
Section: Cohomology Of Lie Algebras With Involutionmentioning
confidence: 99%
“…Two consequences of [117] are that finite dimensional von Neumann algebras and abelian von Neumann algebras have the property that every triple derivation into the predual is an inner triple derivation, analogous to the Haagerup result. This property was called normal ternary weak amenability in [205] where it is shown that it rarely holds in a general von Neumann algebra, but that it comes close. The main results of [205] are the following two theorems.…”
Section: Triple Derivations On Von Neumann Algebrasmentioning
confidence: 99%
“…This property was called normal ternary weak amenability in [205] where it is shown that it rarely holds in a general von Neumann algebra, but that it comes close. The main results of [205] are the following two theorems. The first one gives a cohomological characterization of finite factors and the second gives a "zero-one" law for factors.…”
Section: Triple Derivations On Von Neumann Algebrasmentioning
confidence: 99%